Dual-Pathway Service Quality dan Pembentukan Kepercayaan Mitra: Peran Mediasi Kepuasan dalam Industri Jasa Pelabuhan - Mario Ricci Mangu; Sefnedi Sefnedi; Kasman Karimi (Politeknik Ganesha Medan, 2026)
This study investigates how trust is formed among business partners in the port service industry, where variability in service performance and coordination complexity may generate relational uncertainty. Addressing the need to better understand relational mechanisms in B2B port services, this research examines the dual-pathway effect of service quality on partner trust formation, with customer satisfaction serving as a mediating mechanism. Grounded in relationship marketing and service quality theory, the study employs a quantitative approach to analyze how the technical and functional dimensions of service quality influence trust both directly and indirectly through satisfaction. Primary data were collected using structured questionnaires from 125 business partners of a major Indonesian port authority, including shipping agents, logistics firms, and cargo operators engaged in ongoing contractual relationships. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that service quality has a significant positive effect on customer satisfaction and partner trust. Customer satisfaction also exerts a strong positive influence on trust and partially mediates the relationship between service quality and trust. These results demonstrate that trust in port service relationships is shaped through a dual pathway: direct evaluations of service performance and affective responses reflected in satisfaction levels. By positioning satisfaction as a central relational mechanism, this study extends the service quality literature by offering a process-based explanation of trust formation in B2B port services. Practically, the findings suggest that port authorities and service operators should prioritize consistent service reliability, responsiveness, and professionalism while simultaneously managing partner satisfaction to strengthen long-term collaborative relationships.